The Road to War: Overview of the Political Situation in Bosnia and Herzegovina between Spring 1990 and Spring 1992 - Aleksić, Jovan J. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The very end of the ninety nineties brought tectonic changes throughout Europe, such as the fall of the Berlin wall and German reunification, dissolution of the Warsaw Pact, collapse of the Soviet Union. All those happenings were believed to have a strong impact on further events of Yugoslav policy. The downfall of Communism in Eastern Europe also triggered the Communism crisis in Yugoslavia as well as the existence of the Socialist Federal Republic of Yugoslavia as a unity, along with the socio-economic crisis that had not been dying away by the end of the nineties of the twentieth century. Bosnia and Herzegovina was the Constituent Federal Unit of Yugoslavia, and according to its constitution it represented an “entity unto itself”. Placed between the eastern and western part of the country, it was considered to be the place where people of three different nations lived, along with three different religions rich in history and culture, coexisting together in harmony, as well as in bigotry, conflicts, and extermination. Every attempt to introduce the multiparty system in Bosnia and Herzegovina had been denied by the League of Communist authorities, even when it seemed obvious. Communist leaders of Bosnia and Herzegovina were especially sensitive to anz behaviour on a national basis, they thought that this would cause further ethnic divisions. Nevertheless, it was bound to happen sooner or later. In 1990, three ethnic parties were formed (Serbian Democratic Party, Bosnian Democratic Action Party, Croatian Democratic Union), soon to become “Ethnic movements of Serbs, Muslims, and Croats”. All three obtained absolute minority in the elections and formed certain government authority. However, all parties had three completely different party (agenda) models, three completely different goals. Serbian government spokesmen declared themselves to stay in united Yugoslavia, Croats were against it, while Muslims declared themselves to be more dominant than they used to be. It was obvious that the destiny of Bosnia and Herzegovina was directly depended on the destiny of Yugoslavia. That was how disintegration of Yugoslavia prejudged disintegration of Bosnia and Herzegovina. Secession of Slovenia and Croatia directly increased tensions in Bosnia and Herzegovina and affected its future position. Allied with Croats, Muslims were determined to walk out of Yugoslavia, while the Serbs were persistent in their intention to stay in at any cost. After a series of unsuccessful sessions and negotiations, Muslim and Croatian political representatives wanted a referendum of independence, contrary to the Serbian will, who later on proclaimed a process of formation of their own republic. Last attempt to facilitate the ongoing crisis in Bosnia and Herzegovina was made in Lisbon, along with mediation of the European Community and its representatives, Jose Cutileiro and Lord Carrington. Although their compromise proposal initially accepted by all three parties, Alija Izetbegovic, ten days later, on 28th of March 1992, after talks with US Ambassador to Yugoslavia, Warren Zimmermann, rejected the peace plan. That is how the last attempt to stop warfare collapsed. Bosnia and Herzegovina rushed into war